Hydrothermal Alteration of the Ocean Crust and Patterns in Mineralization With Depth as Measured by Micro‐Imaging Infrared Spectroscopy. Issue 8 (24th August 2021) - Greenberger, Rebecca N.; Harris, Michelle; Ehlmann, Bethany L.; Crotteau, Molly A.; Kelemen, Peter B.; Manning, Craig E.; Teagle, Damon A. H.; ,
Abstract: Processes for formation, cooling, and altering Earth's ocean crust are not yet completely understood due to challenges in access and sampling. Here, we use contiguous micro‐imaging infrared spectroscopy to develop complete‐core maps of mineral occurrence and investigate spatial patterns in the hydrothermal alteration of 1.2 km of oceanic crust recovered from Oman Drilling Project Holes GT1A, GT2A, and GT3A drilled in the Samail Ophiolite, Oman. The imaging spectrometer shortwave infrared sensor measured reflectance of light at wavelengths 1.0–2.6 μm at 250–260 μm/pixel, resulting in >1 billion independent measurements. We map distributions of nine key primary and secondary minerals/mineral groups—clinopyroxene, amphibole, calcite, chlorite, epidote, gypsum, kaolinite/montmorillonite, prehnite, and zeolite—and find differences in their spatial occurrences and pervasiveness. Accuracy of spectral mapping of occurrence is 68%–100%, established using X‐ray diffraction measurements from the core description. The sheeted dikes and gabbros of upper oceanic crust Hole GT3A show more pervasive alteration and alteration dominated by chlorite, amphibole, and epidote. The foliated/layered gabbros of GT2A from intermediate crustal depths have similarly widespread chlorite but more zeolite and little amphibole and epidote. The layered gabbros of the lower oceanic crust (GT1A) have remnant pyroxene and 2X less chlorite, but alteration is extensive within and surrounding major fault zones with widespread occurrences of amphibole. The results indicate greater distribution of higher temperature alteration minerals in the upper oceanic crust relative to deeper gabbros and highlight the importance of fault zones in hydrothermal convection in the lower ocean crust. Plain Language Summary: The oceanic crust, the rock from the ocean floor to the mantle, forms much of Earth's solid crust, yet it is difficult to access, drill into, or collect samples from. This kilometers‐thick crust forms from cooling of molten rock, but we do not entirely understand how it forms, cools, and changes by chemical reactions with water. Ophiolites are places where rock from the ocean crust and uppermost portion of the mantle have been pushed upward and exposed on continents. One such location is in Oman, where the Oman Drilling Project drilled into continuous sections of ocean crust. We measured this drill core with imaging spectroscopy, a technique where we measure how infrared light at hundreds of wavelengths reflects off the rock. We use the characteristic infrared fingerprints of minerals to map them at sub‐millimeter scale, producing over one billion measurements. We find that much of the rocks closer to the ocean reacted with water at high temperatures to form new minerals. Some rocks deep within the ocean crust also interacted with large volumes of water, but intense fluid flow was concentrated in fractures and smaller areas, leaving less reacted rock. Key Points: Imaging spectroscopy efficiently and effectively mapped spatial patterns in hydrothermal alteration mineral occurrence in ocean crust core Samail ophiolite upper ocean crust cores are dominated by chlorite, amphibole, and epidote, while deeper cores have more zeolite/prehnite Hydrothermal alteration largely decreases with depth in the ocean crust but is locally intense in major fault zones, even in lower crust